PLATELET SEROTONIN UPTAKE IS HIGHER IN EARLY-ONSET THAN IN LATE-ONSET ALCOHOLICS - Javors, Martin; Tiouririne, Mohamed; Prihoda, Thomas (Alcohol and alcoholism (Oxford), 2000)
The main objective of this study was to compare platelet serotonin (5-HT) uptake between early-onset alcoholics (EOA) and late-onset alcoholics (LOA). Subjects were 24 dependent male alcoholic in-patients and 21 healthy control subjects. 5-HT uptake was quantified by incubating platelets with [3H]5-HT at various concentrations (0.5 to 1000 nM). 5-HT uptake was higher in EOA, compared to both the LOA and control groups (P < 0.02) at the highest 5-HT concentration (1000 nM). No significant difference was found between LOA and controls or between EOA + LOA and controls. Previous studies have shown that 5-HT uptake was higher in platelets, lymphocytes, and brain of alcoholics vs controls, but our data suggest that higher platelet serotonin transporter function is limited to EOA, not LOA.